Pengaruh Kualitas Produk, Harga, dan Ekuitas Merek terhadap Keputusan Pembelian Laptop Asus pada Mahasiswa FISIP Universitas Mulawarman - Murtajah Zuliani (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Asus is one of the laptop brands from Taiwan that is widely recognized among students due to its products offering good quality, reliable performance, and competitive pricing, making it popular among students. This study aims to examine the influence of Product Quality, which includes performance, durability, and the features offered. In addition, price plays an important role in the purchase decision, although in some cases it may be influenced by the consumer’s perception of the product's value. Brand Equity includes factors such as brand awareness, brand image, and consumer loyalty, and is also considered a highly influential element in the Purchase Decision of Asus Laptops among students of the FISIP Faculty at Universitas Mulawarman. This study employs a quantitative approach with a survey method. The sampling technique used is probability sampling with a simple random sampling method, involving 98 respondents. Data is collected through questionnaires distributed to FISIP students at Universitas Mulawarman who are users or buyers of Asus laptops. Data analysis is performed using multiple linear regression to determine the relationship and influence between independent variables (product quality, price, and brand equity) and the dependent variable (purchase decision). The results indicate that product quality, price, and brand equity both partially and simultaneously have a positive and significant effect on the purchase decision, meaning that the greater the likelihood of students purchasing an Asus laptop. These findings show that these three variables are key factors influencing consumer behavior in making a purchase decision for Asus laptops. This study provides valuable insight into the factors influencing technology product purchase decisions among students.